Online rheumatology school as an alternative to traditional educational technologies for patients - O. V. Teplyakova; N. B. Poletaeva; A. V. Sarapulova (Современная ревматология)
During the COVID-19 pandemic, many patients with rheumatic diseases were left without specialized care and information support, however, the current level of digitalization makes it possible to transfer the training and education of patients and their relatives to an online format. Objective: to analyze the experience of holding a rheumatological school in an online format as a method of improving the medical literacy of the population.Patients and methods. A cross-sectional study was performed by voluntary anonymous questioning of 157 patients who, from September 2020 to November 2021, took part in the online school on rheumatology held at the Clinical Rheumatology Center "New Hospital" (Yekaterinburg). All patients filled out an online questionnaire that included 15 questions related to age, place of residence, motivation of students, sources of information about the school, assessment of the form and content of lectures, quality and novelty of the information provided, and degree of doctor’s credibility.Results and discussion. Analysis of the results of the survey demonstrated the interest of patients in obtaining high-quality medical information on rheumatology problems, a positive assessment of the format and content of the online school, its positive role in clarifying the essence of the disease and related problems.Conclusion. Online schools for patients seem to be a relevant and promising area of medical prevention.